Vitamin D status during pregnancy and offspring outcomes: a systematic review and meta-analysis of observational studies - Tous, Monica; Villalobos, Marcela; Iglesias-Vázquez, Lucía; Fernández-Barrés, Sílvia; Arija, Victoria (European journal of clinical nutrition, 2020)
Vitamin D deficiency during pregnancy may influence adverse outcomes in offspring. The aim of this systematic review and meta-analysis of observational studies was to assess the association between low prenatal concentrations of 25(OH)D (by using three different cut-off levels), preterm birth (PTB) and anthropometric and neurodevelopmental outcomes in offspring. Studies reporting data on the association between maternal vitamin D concentrations and offspring outcomes identified through a systematic review of scientific literature published in PubMed/MEDLINE, Scopus and the Cochrane Library databases up to April 2017. We included 54 eligible studies. Vitamin D-deficient mothers (<30 nmol/L) had offspring with lower birthweight (MD -87.82 g; 95% CI -119.73, -55.91 g), head circumference (MD -0.19 cm; 95% CI -0.32, -0.06 cm) and a higher risk of small for gestational age (SGA) infants and PTB (OR 1.59; 95% CI 1.24, 2.03) compared to mothers with concentrations ≥30 nmol/L. Vitamin D insufficiency (<50 nmol/L) was associated with a higher risk of SGA and PTB (OR 1.43; 95% CI 1.08, 1.91 and OR 1.28; 95% CI 1.08, 1.52, respectively). Concentrations of 25(OH)D ≥75 nmol/L were not found to be associated with birthweight, SGA or PTB. Offspring of vitamin D-insufficient mothers had lower scores in mental (MD -1.12 points; 95% CI -1.82, -0.42 cm) and language developmental tests (MD -0.35 points; 95% CI -1.00, 0.31 cm). Maternal vitamin D deficiency is associated with offspring adverse anthropometric outcomes and PTB; insufficiency with a higher risk of SGA, PTB and adverse neurodevelopmental outcomes.